Kebijakan Fiskal dan Ekspansi Kredit Perbankan di Indonesia dengan Pendekatan Error Correction Model (ECM) - Wicaksono, Sony; Afin, Rifai (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2016)
This study is aimed to determine how the effect of the fiscal policy on the changes in credit in Indonesia in the period of 1974 until 2013 with the applying of dynamic method of error correction model that show the relationship between the fiscal policy instrument with bank credit in the long term and short term. The approach of this study is quantitative with secondary data that collected from the library visit to Indonesian banks and online search on the World Bank website. Variables used in this study are credit as dependent variable and the ratio of taxes and government spending as independent variables as well as fiscal policy instrument, besides that, this study uses control variables that are money supply and the exchange rate. The results show , the fiscal policy in Indonesia in two instruments namely the ratio of taxes and government spending has a different result in the long term and short term. In the long term, the ratio of taxes has significant negative effect as much as 5.096 percent, while the government spending has significant positive effect as much as 0.638 percent. In the short term, the ratio of taxes does not have significant effect, while the government spending has significant positive effect as much as 0.270 percent. This conclusion is based on the calculation of the estimated results of long term and short term